Perceived stress, physiological stress reactivity, and exit exam performance in a prelicensure Bachelor of Science nursing program. - Brodersen, Lisa; Lorenz, Rebecca (International Journal of Nursing Education Scholarship, 2020)
Objectives: High-stakes exams are a source of chronic stress that may adversely affect nursing students' thinking, behavior, and overall health. The purpose of this study was to explore the relationships of perceived stress, physiological stress reactivity, and exit exam performance. Methods: A within-subjects design allowed measurement of perceived stress, salivary cortisol, and salivary alpha amylase in pre-licensure nursing students under two different conditions: a high-stakes exit exam and a low-stakes homework assignment. Results: Perceived stress and salivary alpha amylase were significantly higher after the high-stakes exam compared to the homework condition. Perceived stress after the exam was correlated with lower exam score. Conclusion: Study findings suggest that in response to a high-stakes exam, prelicensure nursing students experience high levels of perceived stress coupled with sympathetic activation but not activation of the hypothalamic-pituitary adrenal axis.